A Cadaveric Study on the Anomalous Origin of Renal and Gonadal Vasculature: An Observational Study - Penelope C. Farris; Dylan M. Macciola; Lauren N. Barazani; Justin R. Nathan; Danielle Quinn; Daniel F. Peters (University Library System, University of Pittsburgh, 2022)
Background: Due to the increasing prevalence of kidney transplantation, a greater awareness of variations in the surrounding vasculature is of surgical importance. During embryological development, both the renal and gonadal arteries arise from lateral mesonephric branches of the dorsal aorta. In adults, gonadal arteries are paired vessels that normally arise from the aorta at the level of the second lumbar vertebra. Methods: Routine cadaveric dissection completed by first-year medical students and dental students incidentally revealed anatomical anomalies. Results: We describe two cadaveric findings in male cases which demonstrate unilateral and bilateral variations of testicular arteries originating from an aberrant renal artery in one case and an accessory renal artery in the other. Conclusion: By increasing awareness of anomalous testicular arteries we hope to encourage the standardization of preoperative vasculature exploration to both minimize intra-operative risk to living male kidney donors and increase patients' understanding of potential risks and complications prior to consenting to the procedure providing more accurate information prior to surgery.